Risk Factors for Venous Thromboembolism in Adults with Hemoglobin SC or Sβ(+) thalassemia Genotypes - Yu, Tiffany T. (Thromb Res, 2016)
INTRODUCTION: Venous thromboembolism (VTE) is common in sickle cell disease (SCD); however, the risk factors associated with VTE in patients with sickle variant syndromes are not known. The primary aim of this study was to determine hematologic and clinical risk factors for VTE in adults with hemoglobin SC or Sβ(+) thalassemia genotypes. MATERIALS AND METHODS: We conducted a retrospective cross-sectional analysis of patients with hemoglobin SC and Sβ(+) thalassemia genotypes followed at the Sickle Cell Center for Adults from 2008 to 2012. Data on baseline hematologic parameters and SCD-specific comorbidities were collected from review of electronic records. RESULTS: A total of 116 patients, 85 (73%) with hemoglobin SC disease and 31 (27%) with Sβ(+)-thalassemia, were included for analysis. Thirty-two (28%) patients had a verified history of non-catheter related VTE. Mean baseline hemoglobin levels were higher among individuals with a history of VTE compared to those without (11.7 g/dL vs. 11.0 g/dL, p=0.003). In addition, the prevalence of surgical splenectomy was higher among patients with VTE compared to those without (25.0% vs. 4.8%, p=0.001). On multivariate analysis, elevated baseline hemoglobin (odds ratio [OR] 2.45 (95% confidence interval [CI] 1.42–4.23) and history of surgical splenectomy (OR 5.76 [CI 1.43–23.22) were independently associated with VTE risk. CONCLUSIONS: Higher baseline hemoglobin is a risk factor for non-catheter-related VTE in patients with hemoglobin SC or Sβ(+) thalassemia genotypes. Surgical splenectomy, which is a known risk factor for VTE in other hemoglobinopathies such as β-thalassemia intermedia, is also associated with VTE in sickle variant syndromes. Future studies are needed to validate these findings and to investigate the mechanisms of hypercoagulability observed in patients with hemoglobin SC and Sβ(+) thalassemia.